2020
DOI: 10.21203/rs.3.rs-22741/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Submicroscopic malaria infection is not associated with fever in cross-sectional studies in Malawi

Abstract: Abstract Background: Submicroscopic Plasmodium falciparum infections are widespread in many areas. However, the contribution of these infections to symptomatic malaria is not well understood. In this study we evaluated whether participants with submicroscopic P. falciparum infections have higher prevalence of fever than uninfected participants in southern Malawi. Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
1
0
1
Order By: Relevance
“…The majority of infections detected in community-based surveillance are submicroscopic, and these low-density infections are not associated with fever. 8 However, a small proportion of infections causes clinical disease. Through a longitudinal cohort of adults and children at a rural health center, we demonstrated that asymptomatic parasitemia was present in 23% of all visits.…”
Section: Epidemiology Of P Falciparum Infection and Malaria Disease I...mentioning
confidence: 99%
“…The majority of infections detected in community-based surveillance are submicroscopic, and these low-density infections are not associated with fever. 8 However, a small proportion of infections causes clinical disease. Through a longitudinal cohort of adults and children at a rural health center, we demonstrated that asymptomatic parasitemia was present in 23% of all visits.…”
Section: Epidemiology Of P Falciparum Infection and Malaria Disease I...mentioning
confidence: 99%
“…Une autre étude réalisée à Libreville (Gabon) mettra l'accent sur le fait que les ISM à P. falciparum sont fréquents chez les patients symptomatiques bien que leur distribution diffère d'une zone à une autre (4). Une plus ressente étude mener au Malawi sur la population générale et publiée en 2020 n'a pas rapporté d'association entre les ISM à P. falciparum et le risque de faire la fièvre (15). A la lumière de ces résultats, il parait nécessaire de développer des outils diagnostiques adaptés permettant de détecter ces ISM notamment chez les symptomatiques et de mettre en place une reconnaissance clinique de la maladie d'autant plus que ces infections représentent une part importance du réservoir de transmission du paludisme.…”
Section: Ism Chez Les Sujets Symptomatiquesunclassified